The Development of Berbakti: Elder Caring Mobile Application in Indonesia - Septian Enggar Sukmana; Heru Agus Santoso; Fahri Firdausillah; Adhitya Nugraha; Farah Zakiyah Rahmanti; Arkav Juliandri (Politeknik Negeri Batam, 2019)
Children must care their parent as their devotion to their parent. In Indonesia, that kind condition is a common situation. But, to handling this situation in this global era is more difficult because many children choose going to another city or another region to do some activity like taking a job or going to college. It gives an impact to their parent especially when their parent is too old and needs to be cared. This motivation in this paper is based on this kind problem. The development of application uses Waterfall. The system must meet the requirement so not just technichal development is performed, social study must be conducted in the process. We use several testings such blackbox testing, server testing, and usefulness identity. Commonly, we got unsatisfied result based on testing, so some repairement must be conducted.